INDUSTRIAL RELATIONS IN THE PERSPECTIVE OF JUSTICE THEORY BY JOHN RAWLS - Ari Hernawan (Fakultas Hukum Universitas Gadjah Mada, 2014)
Conflict of interest between employee and employer has a complexity since its biopsychology and sosioeconomic in nature. As its implication, it is difficult to create a consensus between two different interest within a legal perspective. Justice theory by John Rawls has answered the respective problem by giving legal priority upon the group of people who have less capacity in sosial and economic. According to John Rawls, law shall give orientation toward marginalized group. In industrial relations, law shall take side upon the employee who are in subordinate position. Pertentangan kepentingan antara pekerja dan pengusaha memiliki kompleksitas karena bersifat biopsikologis dan sosio-ekonomi. Sebagai implikasinya, sulit mempertemukan dua kepentingan yang berbeda tersebut dalam satu rumusan hukum. Teori keadilan dari John Rawls telah menjawab persoalan tersebut dengan memberi prioritas hukum kepada orang-orang yang secara sosial ekonomi kurang beruntung. Hukum menurut John Rawls harus berorientasi kepada kelompok marjinal. Dalam hubungan industrial, hukum harus berpihak kepada pekerja yang berada dalam posisi subordinat.